Supplying Religious Services to Urban Communities: The Revitalization of Muhammadiyah's Da'wah Councilin West Nusa Tenggara - Rahmawati, Endang; Sukarta, Sukarta; Muhammad, Zulkifli (KOMUNIKA, 2025)
This study analyzes the revitalization strategies of Muhammadiyah's Da'wah Council (Majelis Tabligh) in West Nusa Tenggara (NTB) in supplying religious services to urban communities amid growing secularization pressures. Grounded in religious supply theory and capacity building framework, and informed by persuasive communication theory, this qualitative study collected data through in-depth interviews with ten key informants, participatory observation, and document analysis over six months, analyzed using Miles and Huberman's interactive model. Findings reveal four interconnected revitalization strategies: strategic muballigh distribution, establishment of the Muhammadiyah Preachers Corps (2024), intensive training programs, and correctional institution partnerships (2025). Urban da'wah is implemented through community-based approaches, multi-channel digital media platforms, and cultural contextualization respecting Sasak traditions. Communication strategies operationalize Aristotelian ethos-pathos-logos principles, Hovland's Yale persuasion model, and digital adoption patterns consistent with Rogers' Diffusion of Innovation theory. Revitalization outcomes include enhanced Islamic literacy, strengthened community cohesion, maintained Islamic identity, and expanded social capital reaching marginalized groups. The study concludes that effective urban da'wah requires a comprehensive, adaptive, and communicatively grounded institutional strategy—one that integrates organizational capacity building with deliberate multi-channel persuasive communication to remain vitally relevant in modernizing urban contexts.